Gullevers Reisen (Köhl : DuMont, 1991)
Albert, Juri ; Alexander, Leslie ; Anderson, Curtis ; Arienti, Stefano ; Armstrong, L.C. ; Von Arx, Stephan ; Atkinson, Sue ; Atkinson, Terry ; Belcher, Alan ; Belz, Gerd ; Bernstein, Thomas ; Betke, Wolfgang ; Blum, Heiner ; Bôckler, Ursula ; Bolande, Jennifer ; [et al.]
Gullivers Reisen = Gulliver's travels, Galerie Sophie Ungers, Cologne, from April 10 to April 19 1991
boek